(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Experiments were conducted to test the effect of MS saltsconcentration, potassium dihydrogen phosphate and growth regulators onshoot proliferation and growth in grapevine (Vitis vinifera L.), usingexplants derived from in vitro grown plantlets. Murashige and Skoogoriginal medium was used as basal medium. Shoot proliferation occurredprincipally when using nodal stem segments as explants. Among MS-saltstrengths tested, full MS- strength (1X) was optimum for shootproliferation and elongation. Increasing the original phosphorusconcentration in the medium by the addition of 170 mg/L KH2 PO 4 had apositive, marked effect on shoot number and shoot length. The nodal stemsegment explants responded best to relatively low concentrations of NAAand kinetin, and a large number of shoots and good plantlets height wereobtained on the medium containing 0.1mg/L NAA and 1.0 mg/L kinetin.Root formation occurred on the medium containing 0.3 mg/L IBA.